Decoration of Nanofibrous Paper Chemiresistors with Dendronized Nanoparticles toward Structurally Tunable Negative‐Going Response Characteristics to Human Breathing and Sweating. Issue 22 (19th September 2017) - Yan, Shan; Liu, Xin; Skeete, Zakiya; He, Ning; Xie, Zhi‐Hui; Zhao, Wei; Lombardi, Jack P.; Liu, Kai; Kang, Ning; Luo, Jin; Hsiao, Benjamin S.; Poliks, Mark; et al.
Abstract: The development of wearable breath or sweat sensor arrays for human performance monitoring is increasingly important for providing personalized health information under various environmental conditions. A major challenge is the lack of sensing elements responsive uniquely to moisture‐dominated breathing and sweating processes, which is critical for differentiating other chemical or biological species from the moisture‐dominated environment. Here a novel class of nanofibrous paper chemiresistors decorated with dendronized nanoparticles that exhibit structurally tunable and negative‐going responses to human breathing and sweating is reported. The nanocomposite device features flexible membrane‐type scaffold derived from multilayered nanofibrous paper as a biocompatible matrix and dendronized gold nanoparticles with tunable sizes and shapes to enable structural diversity and molecular sensitivity. Key elements of novelty include the immobilization of poly(ether‐ester) dendrons with oligoethylene glycol spacers on gold nanoparticles and the combination of hydrogen bonding and van der Waals interactions between partially interpenetrating dendrons, leading to tunable and unique response characteristics to breathing and sweating processes. The results demonstrate the first example of nanofibrous paper chemiresistors decorated with dendronized nanoparticles as a promising new strategy toward constructing sensing interfaces for wearable breath and sweat sensors. Abstract : A nanostructured paper chemiresistor with negative‐going response dominant characteristics to human breathing and sweating is demonstrated, which involves decoration of a nanofibrous membrane paper with dendronized gold nanoparticles to enable highly tunable sensitivity in moisture‐dominant sensing environment and constitutes a promising new strategy to design sensing array elements for wearable breath and sweat sensors.